INCUBADORAS DE EMPRESAS: ESTÍMULO AO EMPREENDEDORISMO INOVADOR - Manjama, Maria Paulina (2019)
Business Incubators, are propitious environments for the creation of technology-based companies, such as spin off, SartUp's, etc. This is the reason why the innovative activities promoted by this technological environment, lead the entrepreneurs to take advantage of the existing market opportunity. In the period 2007-2017, Brazil went from great economic growth to economic crisis. Does the minimization of notices in support of governmental development or not, in innovative research, university-enterprise, incubators, technological parks, etc., may or not have harmed this environment? The present study carried out an analysis of business incubators and Technological Basis in Brazil and the state of Paraná during the period 2007-2017, as institutions to stimulate entrepreneurship, technological innovation, and stimulation of national and regional socioeconomic development through a quantitative research approach, bibliographic research and exploratory documentary. Brazil has 369 incubators of active companies, which 223 are associated with ANPROTEC. The state of Paraná is home to 21 incubators of companies associated with the network, which are mostly of Technological Base and constitute 9% of Brazilian incubators. Despite the great improvement in incubation processes with the adoption of new management models and practices, launch and creation of new development bids, some factors such as precipitation, budget cuts and lack of planning and adequate policies to create innovative environments led to a drop in the number of associated incubators in the State of Paraná network during the period 2007-2017, in the order of 15%. Was concluded that the number of incubators of companies associated with ANPROTEC in the State of Paraná grew by approximately 23%, which resulted in an increase in jobs and income, and may be related to the increase in incentives for innovation promoted by government bidders or not to foster innovative entrepreneurship in the period 2007-2017.